2021
DOI: 10.1103/physreve.103.062401
|View full text |Cite
|
Sign up to set email alerts
|

Immune phase transition under steroid treatment

Abstract: The steroid hormone, Glucocorticoid (GC) is a well-known immunosuppressant that controls T cellmediated adaptive immune response. In this work, we have developed a minimal kinetic network model of T-cell regulation connecting relevant experimental and clinical studies to quantitatively understand the long-term effects of GC on pro-inflammatory T-cell (Tpro) and anti-inflammatory Tcell (Tanti) dynamics. Due to the antagonistic relation between these two types of T-cells, their longterm steady-state population r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…In the T-cell-mediated immune system context, such theoretical concepts help characterize different immunoregulatory states and their modulation under different environmental situations (Roy et al . 2014 ; Roy and Bagchi 2020 ; Nayak and Roy 2021 ). T-cell-mediated immune regulations are often classified into weak, strong, and moderate regulation regimes based on the ratio and relative concentration of pro-inflammatory T-cells and anti-inflammatory T-cells.…”
Section: Mathematical Models Capturing T-cell Dynamics Of the Human I...mentioning
confidence: 99%
See 4 more Smart Citations
“…In the T-cell-mediated immune system context, such theoretical concepts help characterize different immunoregulatory states and their modulation under different environmental situations (Roy et al . 2014 ; Roy and Bagchi 2020 ; Nayak and Roy 2021 ). T-cell-mediated immune regulations are often classified into weak, strong, and moderate regulation regimes based on the ratio and relative concentration of pro-inflammatory T-cells and anti-inflammatory T-cells.…”
Section: Mathematical Models Capturing T-cell Dynamics Of the Human I...mentioning
confidence: 99%
“…Among these CD4+ T-cells, it has been observed that some act as pro-inflammatory cells (Th1, Th2, Th17, Th9, Th22, and Tfh cells), and others work as anti-inflammatory cells (Th 3 and Treg cells) (Lei et al . 2021 ; Nayak and Roy 2021 ).…”
Section: Experimental Overview Of Dynamic Behaviors Of Cd4+ T-cells: ...mentioning
confidence: 99%
See 3 more Smart Citations